Implementasi Konsep Smart Economy dalam Pengembangan Ekonomi Kreatif di Kabupaten Kutai Kartanegara - Risma Widiyawati; Muhammad Tommy Fimi Putra (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the implementation of the smart economy concept in the development of the creative economy in Kutai Kartanegara Regency. The background of this study is based on the importance of utilizing digital technology, innovation, and creativity in driving sustainable regional economic growth. Kutai Kartanegara Regency has great potential in the creative economy sector, but still faces various obstacles such as limited digital literacy, access to resources, and optimization of technology utilization. The research method used is a qualitative descriptive approach with data collection techniques through interviews, observation, and documentation. Data analysis was carried out using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results show that the implementation of the smart economy in Kutai Kartanegara Regency has been carried out through various creative economy development programs, such as marketing digitalization, business actor training, and government support for MSMEs. The application of this concept can increase innovation, productivity, and competitiveness of creative economy actors. However, several obstacles remain, including the low optimal utilization of digital technology and limited access to resources and marketing networks..